Effect of Public Procurement Audit on Performance of State Corporations in Kenya - Gichuki, Hannah Wangui; Paul, Dr. Samson Nyang'au (International Journal of Supply Chain and Logistics, 2020)
Purpose: The purpose of the study was to assess the effect of public procurement audit on performance of state corporations in Kenya. Methodology: The study employed a descriptive research design, targeting heads of procurement in state corporations. As a rule of thumb when the population is below 200, a study does a census. The researcher preferred this method because it allowed an in-depth study of the subject. Data was collected using self-administered questionnaires. Pilot study was carried out to establish the validity and reliability of the research instruments. The instruments were designed appropriately according to the study objectives. The data collected was analyzed by use of descriptive and inferential statistics. The study used multiple regression and correlation analysis to show the relationship between the dependent variable and the independent variables. The data generated was keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) version 24 to generate information which was presented using charts, frequencies and percentages. Results and conclusion: The findings of the study concluded that preparation and planning auditing, information and publicity auditing, evaluation of received tenders auditing, award and execution of contract auditing have a positive relationship with performance of state corporations in Kenya. The independent variables reported R value of 0.876 indicating that there is perfect relationship between dependent variable and independent variables' square value of 0.768 means that 76.8% of the corresponding variation in performance of state corporations in Kenya can be explained or predicted by (preparation and planning auditing, information and publicity auditing, evaluation of tenders auditing and award and execution of contract auditing) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.761), p=0.000 <0.05). Unique contribution to theory, policy and practice: The study recommended that public institutions should embrace public procurement audit so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained.